Concept Mapping: An Innovative Technique for Easy and Ensured Learning Outcomes - Quazi , Afshan Naz (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Alexandra k Transfer quoted ―The best teachers are those who show you where to look, but don‘t tell you what to see‖. Pedagogy and enriched content are dependable solutions for effective teaching and learning. Real meaningful learning is the focus of modern teaching which follows a constructivist approach. Bygone are the days when the traditional lecture method was sufficient to teach the pupils. Advanced technologies have been the replacement of monotonous lecture methods. The pupil now constructs their knowledge by engagement, exploration, explanation, elaboration, and evaluation. Different pedagogical practices are involved like the Enquiry approach, reflective strategy, collaborative learning, etc. among which concept mapping is one of the important strategies. It is a graphical organizer which connects links between the two or more concepts in some logical sequential flows. Concept mapping effectively assists in achieving the learning outcome which has been already framed by NCERT for each level. Learning Outcomes are the assessment standard that indicates the expected level of learning that children should achieve for that particular class. These are the checkpoints or the minimum levels of learning among the students according to the grade. In class VII, NCERT Science Text contains 18 chapters, among which most of the chapters can be taught impressively with concept mapping, for example, Soil concept map, Heat Concept map, modes of Nutrition in plants, wastewater story, Wind cyclone, and storm concept maps are shown in this paper, which illustrates that concept mapping makes the clear picture in learners mind and it gives assured learning outcome which is expected according to the Module of learning Outcome of NCERT.